Retraction Note: E-Blue: Implementation of an Integrated Blue Economy Ecosystem to Increase Coastal MSMEs Competitiveness (Journal of Indonesian Economy and Business, Vol. 40, No. 2, May, 2025, 10.22146/jieb.v40i2.10994) - Perdana, Tito Aditya; Purusa, Nanda Adhi; Kurniawan, Rudi; Suryawijaya, Tito Wira Eka (Journal of Indonesian Economy and Business, 2025)
The Journal of Indonesian Economy and Business (JIEB) announces the retraction of the article titled "E-Blue: Implementation of an Integrated Blue Economy Ecosystem to Increase Coastal MSMEs Competitiveness", published online on 28 May 2025 in Vol. 40, No. 2 (DOI: 10.22146/jieb.v40i2.10994). Following the detection of numerous inappropriate citations, the editorial team initiated an investigation into the article's content. Upon review, it was concluded that the paper violated the COPE Guidelines on major errors (https://publicationethics.org/guidance/guideline/retraction-guidelines). These issues raised significant concerns regarding the integrity of the article’s research and findings. As a result, the editorial board have agreed to retract the article. The retraction note will be published in JIEB Vol. 40, No. 3 (September 2025).